2014
DOI: 10.1371/journal.pone.0094554
|View full text |Cite
|
Sign up to set email alerts
|

Germline Variation in Cancer-Susceptibility Genes in a Healthy, Ancestrally Diverse Cohort: Implications for Individual Genome Sequencing

Abstract: Technological advances coupled with decreasing costs are bringing whole genome and whole exome sequencing closer to routine clinical use. One of the hurdles to clinical implementation is the high number of variants of unknown significance. For cancer-susceptibility genes, the difficulty in interpreting the clinical relevance of the genomic variants is compounded by the fact that most of what is known about these variants comes from the study of highly selected populations, such as cancer patients or individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 77 publications
1
69
1
Order By: Relevance
“…These genomes were compared to 1,507 adult members of the Inova Translational Medicine Institute (ITMI) pre-term birth cohort also sequenced on the Complete Genomics platform (Bodian et al, 2014). Individuals from these cohorts were filtered to retain only individuals of 95+% European ancestry and a maximum relatedness of 12.5% (see Experimental Methods ).…”
Section: Resultsmentioning
confidence: 99%
“…These genomes were compared to 1,507 adult members of the Inova Translational Medicine Institute (ITMI) pre-term birth cohort also sequenced on the Complete Genomics platform (Bodian et al, 2014). Individuals from these cohorts were filtered to retain only individuals of 95+% European ancestry and a maximum relatedness of 12.5% (see Experimental Methods ).…”
Section: Resultsmentioning
confidence: 99%
“…The p.Arg621Ser variant was also found in an AA subject in an ancestrally diverse cohort of 681 healthy individuals [51]. A previous study involving Japanese patients with Rb found that a majority of the somatic mutations were found in the adenovirus early region 1A (ElA) binding sites [52]; however, the p.Arg621Ser and p. Leu819Val variants have not been reported in any domestic report in patients with Rb.…”
Section: Retinoblastomamentioning
confidence: 99%
“…Biological parentage was confirmed genomically, and ancestry was computed from the genomic data as described. 10 State NBS results, confirmatory tests, and clinical diagnoses of NBS disorders were manually extracted from the neonates' EHR. Data not available from the EHR were obtained from the pediatrician of record when possible and from longitudinal health surveys from the First 1,000 Days of Life Study.…”
Section: Materials and Methods Study Participants And Clinical Datamentioning
confidence: 99%
“…10 The discordance rate of variant calls in the NBS genes in 66 infants sequenced by both CG and Illumina is 0.00277, 95% confidence interval (0.00258, 0.00295) for single-nucleotide polymorphisms and 0.0134, 95% confidence interval (0.0123, 0.0146) for indels (Supplementary Figure S1 online) (the Illumina genomes for these 66 infants were used only for the concordance-rate calculation, not the other analyses presented).…”
Section: Observedmentioning
confidence: 99%